Murine models of diabetic nephropathy - Peters, Verena; Schmitt, Claus P. (Experimental and clinical endocrinology & diabetes, 2012)
Diabetic nephropathy is the leading cause of end stage renal diseases worldwide. Even though several diabetic animal models exist, not a single one develops renal changes sufficiently reflecting those seen in humans. This review provides an overview on mouse models presenting with various features of diabetic nephropathy. The critical analysis and comparison of existing mouse models substantially enhances our understanding of the disease process and should provide a guide for choosing the most suitable mouse model for the investigation of diabetic nephropathy.